A Witness of the Era: A New Biography of Slovak Writer Pavol Strauss (1912–1994): Ivan A. Petranský: Pavol Strauss a jeho 20. storočie [Pavol Strauss and his 20th century]. Bratislava, Marenčin PT, 2025, 572 p. ISBN: 978-80-5569-1379-6 - Bakuła, Bogusław (Slavica, 2026)
Petranský’s book Pavol Strauss a jeho 20. storočie [Pavol Strauss and his 20th century] is a comprehensive biography of the eminent Slovak poet Pavol Strauss (1912–1994), an essayist and aphorist who had been associated with Catholic literary circles since 1946. Pavol Strauss came from a Jewish, intellectual family. From his childhood, he showed an aptitude for literature and music. In the 1930s, he completed his medical studies at a German university in Prague, where he also made his literary debut with two volumes of poetry in German. Before the World War II, he returned to Slovakia, where he began working as a doctor. In the early 1940s, he was baptised into the Catholic faith, which may have saved him from the Holocaust, and in the mid-1940s he began writing in Slovak. He chose to become a Slovak writer, combining literature with his work as a surgeon in hospitals. In the late 1940s, he was persecuted by the security services. He was subject to a ban on publication in Slovakia for almost the rest of his life. He published sporadically in Slovak Catholic publications and in Rome. Despite the repression, he continued to write and became increasingly respected within literary circles. In the 1970s and 1980s, he also became involved in the Catholic samizdat movement. Petranský’s biography draws on numerous previously unknown sources, including material from family archives, the security services’ archives, and the Vatican archives. Petranský paints a highly detailed picture of the era of totalitarianism and the situation of a man living by moral principles that remained unshaken by the tragic events of the time. The portrait of the life of this poet and essayist, whose work was only recognised after his death, is also a portrait of Slovakia’s post-war history. Strauss began his life as a citizen of Austria–Hungary and ended it as a citizen of independent Slovakia. He witnessed great historical changes and bore witness to them in his work. Today, he ranks among the most outstanding Slovak writers associated with the Catholic movement.